Pengembangan sistem informasi kepegawaian berbasis web pada PT XYZ - Santosa, Stefen Wijaya; Dafid, Dafid (Universitas Multi Data Palembang, 2024)
The personnel information system at PT This system aims to provide an efficient means of managing personnel data, including employee leave, punishment, and the recruitment process for prospective employees at PT XYZ. By implementing this system, the main goal is to improve the company's performance in managing personnel information. This system was planned and developed using the Rational Unified Process (RUP) method, with a website-based approach as a prototype. The stages include Inception, Elaboration, Construction, and Transition. The needs analysis process is carried out by collecting information from documents and conducting interviews related to ongoing business processes. The implementation of this design is the development of a web-based application. Apart from that, in making this application, the PHP programming language, code igniter and MySQL database were used. The conclusion from implementing this system is the hope of increasing efficiency in managing personnel information at PT XYZ.